Characterization of porous solids VII : proceedings of the 7th International Symposium on the Characterization of Porous Solids (COPS-VII), Aix-en-Provence, France, 26-28 May 2005 - Llewellyn, P. L. (Philip Leslie) (Studies in surface science and catalysis, 2007)
The 7th International Symposium on the Characterization of Porous Solids (COPS-VII) was held in the Congress Centre in Aix-en-Provence between the 25th-28th May 2005. The symposium covered recent results of fundamental and applied research on the characterization of porous solids. Papers relating to characterization methods such as gas adsorption and liquid porosimetry, X-ray techniques and microscopic measurements as well as the corresponding molecular modelling methods were given. These characterization methods were shown to be applied to all types of porous solids such as clays, carbons, ordered mesoporous materials, porous glasses, oxides, zeolites and metal organic frameworks. * 36 oral presentations and 166 posters and around 230 guests from 27 countries. * A large part of this symposium was devoted to the use computational methods to characterise porous solids.